FRI0158 The conversion of quantiferon TB gold test during biological treatment by anti-TNF preparations. (23rd January 2014) - Zanova, E.; Kozakova, D.; Rybar, I.; Solovic, I.; Rovensky, J.
Abstract : Background: The positivity of QuantiFERON–TB Gold In–Tube test (QFT- G IT) may means the diagnosis of latent tuberculosis (TB), may persists after chemoprophylaxis or may persists as false positivity. Objectives: The interferon gamma release assay tests (IGRA) are useful tools for the diagnostic of latent form of tuberculosis (LTBI) in biological treatment, especially in BCG vaccinated population. The result of QFT-G IT may be positive, negative or indeterminate. We observed the change of originally negative results to positive results in patients with biological treatment. In our work, we would like to determine the number of seroconversions of originally QFT- G IT negative results to QFT- G IT positive results in patients treated in 2011. Methods: The latent Mycobacterium tuberculosis infection in blood was determined by QFT- G IT (IGRA - ELISA test with special blood collection tubes coated with TB antigens, cellestis). Results: We examined 924 patients with biological treatment in National Institute of Rheumatic Diseases, Piestany in 2011. Negative results were found in 807 patients (87.34%), positive results in 117 patients (12.66%). From 117 positive QFT- G IT results were 76 first detected (new patients) and 41 repeatedly detected as positive (from 2008-2010). From 41/117 tests (35.00%) had 18/41 patients repeatedly positive QFT- G IT results from 2008. 23/41 patients had negative QFT- G IT results in the introduction of anti-TNF treatment during 2008-2010 and in 2011 they showed a positive QFT- G IT results. It is 23/117 patients (20.00%) with positive results after previous negativity (23/924; 2.50%) – dominated by women (20/23), according to decade of age with a maximun of 50 years in the decade (10/23). With respect to anti-TNF treatment prevailed conversion of QFT- G IT during the treatment by etanercept (9/23) and adalimumab (8/23). Conclusions: The seroconversion of QFT- G IT during the biological treatment was detected in 23/924 patients with negativity of the entrance test in 2008-2010. The couse could be the contact of the patient with TB during the treatment – newly identified LTBI or the false positivity caused in preanalytical phase. Comments: According to the Guideline of main pneumonologist for the biological treatment in Slovak Republic, demonstrated presence of QFT- G IT positivity after input negativity of this test means the start of chemoprophylaxis treatment during 6 months or during 3 months INH and RIF or during 4 months RIF. References: Use of interferon-gamma release assays in support of TB diagnosis. Stockholm:ECDC, 2011 Diel, E., Wrighton-Smith, P., Zellweger, J-P. Cost-effectiveness of IGRA testing for the treatment of latent tuberculosis in Switzerland, Eur Respir J 2007, 30: 321- 332 Berlinger, Ch., Dudler, J., Mottet, Ch., Nicod, L., Seibold, F., Villiger, P.M., Zellweger, J.P. Screening for tuberculosis infection before initiation of anti-TNF-α therapy. Swiss Med. WKLY 2007, 137: 621-622 Kharbanda, P, Dagaonkar, R., Balakrishnan, C., Udwadia, Z.F. Tumor necrosis factor – α blocker induced tuberculosis. J. Rheumatol 2010, 37: 7-11, www.depts.washington.edu/.../case4/discussion.html Disclosure of Interest: None Declared